DETERMINANTS OF BEHAVIORAL INTENTION TO USE BITCOIN IN MALAYSIA - Farris Ian Gillies; Chun-Teck Lye; Lee-Ying Tay, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2020)
Bitcoin is an emerging digital asset and is getting more attention in the media as of writing. Though, despite the regulatory matters, this paper is more concerned with the factors that influence the behavioral intention to use Bitcoin by the Malaysian. Although there are some recent studies on the intention and acceptance of Bitcoin, yet there is limited evidence from Malaysia. Therefore, this study intends on shedding some light on the current stance of the Malaysians on Bitcoin by examining the factors that affect the behavioral intention to use Bitcoin in Malaysia grounded on the Unified Theory of Acceptance and Use of Technology (UTAUT) model. The data was collected using an online self-administered questionnaire through the relevant local Malaysian forums and local cryptocurrency groups. The result shows that performance expectancy has the greatest influence on the users’ behavioral intention to use Bitcoin, followed by other factors such as social influence and facilitating conditions. Additional analysis of variance and moderation analyses show no significant difference in the mean of the behavioral intention between different demographic characteristics, and the interactions of the demographic characteristics and the UTAUT factors also demonstrate an insignificant effect on the behavioral intention to use Bitcoin. The result suggests that the behavioral intention to use Bitcoin by the Malaysian may increase if the use of Bitcoin can provide convenience to the public and businesses, but it is also influenced by the social and facilitating conditions. The result well reflects the main function of Bitcoin, that is as a currency and also as an investment tool. The finding echoes the effort and policies of the government of Malaysia to find an equilibrium between the use and the abuse of digital currencies as a currency, as well as the risks and returns of digital currencies as an investment tool.